Position paper for guiding response to non-suicidal self-injury in schools - Hasking, Penelope; Heath, N.; Kaess, M.; Lewis, S.; Plener, P.; Walsh, B.; Whitlock, J.; Wilson, M. (Sage Publications, 2016)
Around the world, school staff are increasingly expressing concern about nonsuicidal self-injury (NSSI) and how best to address this behavior in the school setting. However, there is a notable lack of informed guidance for schools, and clear inconsistencies in the practices school staff adopt. In this position paper we draw on our collective research and clinical expertise to provide best-practice guidelines for addressing NSSI in school settings. We outline the importance of a school protocol, and the key features all school protocols should contain. We also focus on how schools can minimize contagion of NSSI within their school environment. We believe these guidelines will be an important starting point for schools interested in developing an evidence-based approach to addressing NSSI.